Preparation method and application of electromagnetic shielding film material with photochromic effect

By introducing PWA and silver nanowire conductive networks on the PMMA substrate, a composite film with a "sandwich" structure is formed, which solves the problem of difficult to take into account both electromagnetic shielding performance and light transmittance in the prior art, and achieves efficient electromagnetic shielding and excellent photochromic effect.

CN119751937AActive Publication Date: 2025-04-04SHAANXI UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411977724.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The prior art lacks thin film materials that can have both excellent electromagnetic shielding performance and light transmittance, especially in application scenarios where photochromic effects are required.

Method used

The composite film with a "sandwich" structure is formed by introducing phosphotungstic acid (PWA) on a polymethyl methacrylate (PMMA) substrate and fixing the conductive network of silver nanowires onto the PMMA substrate by spraying and hot pressing.

Benefits of technology

The composite film has achieved dual optimization of electromagnetic shielding performance and light transmittance, with photochromic effect, and the silver nanowire network is effectively protected to avoid oxidation and shedding, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751937A_ABST
    Figure CN119751937A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an electromagnetic shielding film material with a photochromic effect, which comprises the following steps: adding a mixed solution obtained by mixing phosphotungstic acid particles and tetrahydrofuran into a polymethyl methacrylate dissolving solution, and magnetically stirring to obtain a P-PW12 mixed solution; the silver nanowire dispersions are diluted to different concentrations in an ethanol solution to form a plurality of silver nanowire suspensions, and the concentration range of the different concentrations is 1 mg / mL-5 mg / mL; pouring the P-PW12 mixed solution into a culture dish to obtain a cast film; a part of the cast film is cut into a plurality of parts, each part is correspondingly sprayed with the silver nanowire suspension liquid with one concentration, a P-PW12 / AgNWs-x composite film is obtained, and x corresponds to the concentration of AgNWs; and respectively forming upper and lower substrates on the other parts, respectively arranging the upper and lower substrates on the two sides of each P-PW12 / AgNWs-x composite film, and carrying out hot pressing to obtain the P-PW12 / AgNWs / P-PW12-x composite film containing different AgNWs concentrations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic shielding reflective materials, and in particular to a method for preparing an electromagnetic shielding film material with a photochromic effect. Background Art

[0002] Currently, photochromic materials based on polyoxometalates have been widely used in different application fields, such as optical memory, smart windows, and UV sensors. Polyoxometalate phosphotungstic acid (PWA) has been incorporated into many hybrid matrices to provide the required properties for composite materials. In recent years, people's interest has been focused on polymer matrices, such as polyacrylamide (PAM) and polyvinylpyrrolidone (PVP), etc. Polymethyl methacrylate (PMMA), a well-known thermoplastic polymer for engineering plastics and polymer glasses, is a good choice. It has a wide range of applications, mainly due to its high transparency, thermal stability, good impact resistance and the ability to incorporate a large number of additives.

[0003] Among them, Espindola et al. studied the combination of PMMA and PWA to prepare photochromic films, showing that these highly transparent and photosensitive photochromic films as cast coatings and inkjet printing have broad application prospects. However, they lack specific shielding effects. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method and application of an electromagnetic shielding film material with a photochromic effect, wherein PMMA particles are used as raw materials, dissolved in dichloromethane, and a photochromic material PWA is introduced at the same time, and mixed in a tetrahydrofuran (THF) organic solution to finally form a photochromic film. An interconnected silver nanowire conductive network with a welded joint is fixed on a PMMA substrate by spraying and hot pressing.

[0005] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:

[0006] A method for preparing an electromagnetic shielding film material having a photochromic effect comprises the following steps:

[0007] The mixture of transition metal oxide and polar organic solvent is added to polymethyl methacrylate solution and stirred magnetically to obtain P-PW 12 Mixing solutions;

[0008] Diluting the silver nanowire dispersion in an ethanol solution to different concentrations to form a plurality of silver nanowire suspensions, wherein the different concentrations range from 1 mg / mL to 5 mg / mL;

[0009] In a petri dish, pour P-PW 12mixing the solutions to obtain a cast film;

[0010] Part of the cast film is cut into several pieces, and a silver nanowire suspension of a certain concentration is sprayed on each piece to obtain P-PW 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs;

[0011] The rest of the parts form upper and lower substrates, which are respectively arranged on each P-PW 12 / AgNWs-x composite film on both sides, hot pressing, to obtain P-PW containing different concentrations of AgNWs 12 / AgNWs / P-PW 12 -x composite film.

[0012] Furthermore, the method also includes the preparation of a polymethyl methacrylate solution, specifically, the polymethyl methacrylate particles and a halogenated hydrocarbon solvent are mixed and stirred to be uniformly dispersed, and then the polymethyl methacrylate solution is added, and magnetic stirring is performed to obtain a P-PW12 mixed solution.

[0013] Furthermore, the mass ratio of the phosphotungstic acid particles to the polymethyl methacrylate particles is 15:1-25:1.

[0014] Furthermore, the transition metal oxide includes phosphotungstic acid particles, and the polar organic solvent includes tetrahydrofuran, dichloromethane, acetone, ethyl acetate or N,N-dimethylformamide.

[0015] Furthermore, the magnetic stirring time is 3-7 min, and the speed is 400-600 rpm.

[0016] Furthermore, the P-PW 12 The mixed solution has a solid content of 0.08 mg / mL to 0.1 mg / mL.

[0017] Furthermore, during the spraying, the cast film is fixed on a tinplate sheet that is heated at a constant temperature, and the temperature of the constant temperature heating is 60-80°C.

[0018] Furthermore, during spraying, the distance between the spray gun and the film is at least 9-12 cm, and the spraying pressure is 0.2-0.5 MPa.

[0019] On the other hand, the P-PW obtained by the above-mentioned preparation method of the electromagnetic shielding film material having a photochromic effect 12 / AgNWs / P-PW 12 - Application of x composite films in the field of electronic equipment.

[0020] Furthermore, the application is specifically used as a screen, and the screen can be used in different light environments by adjusting the transmittance state.

[0021] The present invention has the following beneficial effects:

[0022] The preparation method of the present invention produces a film with excellent electromagnetic shielding performance and light transmittance, and has a photochromic effect. By controlling the loading amount of silver nanowires, the optical properties and electromagnetic shielding properties of the composite film can be jointly regulated. At the same time, it is hot-pressed with another layer of PMMA film to form a "sandwich" structure with an interlayer to protect the silver nanowires from oxidation and falling off. A polymethyl methacrylate / phosphotungstic acid electromagnetic shielding composite film (P-PW12 / AgNWs / P-PW12) with a photochromic effect was successfully prepared. This chapter characterizes and analyzes the various properties of the composite film. The prepared composite film not only has high light transmittance and good mechanical strength, but also has an excellent photochromic effect.

[0023] The present invention uses PMMA as a substrate, which not only has the good mechanical properties of traditional polymer materials, but also has the advantage of high light transmittance.

[0024] The present invention uses silver nanowires as conductive fillers, and loads the silver nanowire conductive network on a PMMA substrate by adopting spraying and hot pressing techniques, thereby achieving electromagnetic shielding performance of the material.

[0025] The present invention uses a typical sandwich structure of a film to wrap the silver nanowire network, avoiding displacement and corrosion caused by contact between the conductive network and moisture and oxygen in the air, which gives the material reliable durability, thereby making the material have certain anti-oxidation properties and improving the service life of the composite film.

[0026] The present invention introduces the photochromic material phosphotungstic acid to give the material excellent photochromic properties. The composite film changes from colorless to blue after being irradiated with ultraviolet light, and the photochromic effect is reversible. After repeated color change and color re-color cycles for 10 times, the photochromic performance has no obvious attenuation, showing excellent anti-fatigue performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1a is a network structure diagram composed of silver nanowires (AgNWs);

[0028] Figure 1b P-PW 12 / AgNWs / P-PW 12 -x smooth surface covering layer structure diagram;

[0029] Figure 1c The prepared P-PW 12 / AgNWs / P-PW 12 Cross-sectional view of the composite film;

[0030] Figure 1dIt is the X-ray spectrum of tungsten and phosphorus under energy dispersion;

[0031] Figure 1e It is the X-ray spectrum of tungsten under energy dispersion;

[0032] Figure 1f is the X-ray spectrum of phosphorus under energy dispersion;

[0033] Figure 2a P-PW in the stress-strain curve 12 / AgNWs / P-PW 12 -1 Curve strain diagram of different concentrations;

[0034] Figure 2b The tensile stress data diagram for different AgNWs concentrations in the tensile stress bar graph and strain line;

[0035] Figure 2c The prepared P-PW 12 / AgNWs / P-PW 12 One of the schematic diagrams of the structure of the composite membrane;

[0036] Figure 2d The prepared P-PW 12 / AgNWs / P-PW 12 Schematic diagram of the structure of the composite membrane (II);

[0037] Figure 3a The prepared P-PW with different concentrations 12 / AgNWs / P-PW 12 Transmittance variation diagram of composite film;

[0038] Figure 3b The prepared P-PW 12 / AgNWs / P-PW 12 Transmittance variation of composite film at concentrations of 1-2 mg / mL;

[0039] Figure 3c The prepared P-PW 12 / AgNWs / P-PW 12 Photograph of the composite film on the first reference;

[0040] Figure 3d The prepared P-PW 12 / AgNWs / P-PW 12 Photograph of the composite film on the second reference;

[0041] Figure 3e The prepared P-PW 12 / AgNWs / P-PW 12Photographs of composite films on the third reference;

[0042] Figure 4a P-PW before hot pressing 12 / AgNWs and P-PW 12 / AgNWs / P-PW 12 -x resistance change trend chart;

[0043] Figure 4b For different concentrations of P-PW 12 / AgNWs / P-PW 12 EMI change curve diagram;

[0044] Figure 4c P-PW corresponding to different concentrations of AgNWs 12 / AgNWs / P-PW 12 The change diagram of shielding effectiveness;

[0045] Figure 4d P-PW 12 / AgNWs / P-PW 12-4 Shielding performance change diagram;

[0046] Figure 5a It is the temperature variation curve when the voltage gradually increases and decreases;

[0047] Figure 5b It is the temperature variation curve when the voltage point data increases and decreases;

[0048] Figure 5c It is a temperature variation curve when the voltage is gradually increased and decreased;

[0049] Figure 5d This is the infrared thermal imaging image of the composite film;

[0050] Figure 5e This is the temperature change distribution diagram when the voltage is constant;

[0051] Figure 6a One of the schematic diagrams of the photochromic properties of the P-PW12 / AgNWs / P-PW12 composite film;

[0052] Figure 6b The second schematic diagram of the photochromic performance of the P-PW12 / AgNWs / P-PW12 composite film;

[0053] Figure 6c The third schematic diagram of the photochromic performance of the P-PW12 / AgNWs / P-PW12 composite film;

[0054] Figure 6dThe fourth schematic diagram of the photochromic performance of the P-PW12 / AgNWs / P-PW12 composite film;

[0055] Figure 6e P-PW is irradiated with ultraviolet light 400-800nm 12 / AgNWs / P-PW 12 -3 UV-vis absorption spectrum of composite film;

[0056] Figure 6f P-PW after different times of cycling 12 / AgNWs / P-PW 12 -3 Absorbance change diagram of composite film. DETAILED DESCRIPTION

[0057] The present invention is described in detail below in conjunction with the various embodiments shown in the accompanying drawings, but it should be noted that these embodiments are not limitations of the present invention, and any equivalent transformations or substitutions in functions, methods, or structures made by ordinary technicians in the field based on these embodiments are all within the scope of protection of the present invention.

[0058] Referring to Figures 1-6, the present invention is centered on transparent electromagnetic shielding materials, and on this basis, photochromic functions are added to prepare polymer-based electromagnetic shielding composite films with photochromic effects. PMMA particles are used as raw materials, dissolved in dichloromethane, and photochromic materials PWA are introduced at the same time, and mixed in tetrahydrofuran (THF) organic solution to finally form a photochromic film. The interconnected silver nanowire conductive network with welded joints is fixed on the PMMA substrate by spraying and hot pressing.

[0059] In view of this, it is necessary to design and prepare a film with excellent electromagnetic shielding performance and light transmittance, and also with photochromic effect. By controlling the loading amount of silver nanowires, the optical properties and electromagnetic shielding properties of the composite film can be jointly regulated. At the same time, it is hot-pressed with another layer of PMMA film to form a "sandwich" structure with an interlayer to protect the silver nanowires from oxidation and falling off. The polymethyl methacrylate / phosphotungstic acid electromagnetic shielding composite film (P-PW) with photochromic effect was successfully prepared. 12 / AgNWs / P-PW 12 ). This chapter characterizes and analyzes the various properties of the composite film. The prepared composite film not only has high light transmittance and good mechanical strength, but also has excellent photochromic effect.

[0060] The method for preparing the electromagnetic shielding film material with photochromic effect in the present invention is characterized by comprising the following steps:

[0061] The first step is to prepare a polymethyl methacrylate solution, specifically, the polymethyl methacrylate particles and a halogenated hydrocarbon solvent are mixed and stirred to disperse uniformly, and then the polymethyl methacrylate solution is added, and magnetic stirring is performed to obtain a P-PW12 mixed solution. The mass ratio of the phosphotungstic acid particles to the polymethyl methacrylate particles is 15:1-25:1.

[0062] In the second step, the mixed solution of transition metal oxide and polar organic solvent is added to the polymethyl methacrylate solution, and magnetic stirring is performed to obtain a P-PW12 mixed solution; at this time, the transition metal oxide includes phosphotungstic acid particles, the polar organic solvent includes tetrahydrofuran, dichloromethane, acetone, ethyl acetate or N,N-dimethylformamide; the halogenated hydrocarbon includes dichloromethane.

[0063] In this embodiment, the purpose of using magnetic stirring is to promote the mixing of phosphotungstic acid and polymethyl methacrylate solution to obtain P-PW 12 Mix the solution. The magnetic stirring time is 3-7 minutes and the speed is 400-600 rpm.

[0064] The third step is to dilute the silver nanowire dispersion in an ethanol solution to different concentrations to form a plurality of silver nanowire suspensions, wherein the different concentrations range from 1 mg / mL to 5 mg / mL;

[0065] Step 4: Pour P-PW into the culture dish 12 Mix the solutions to obtain a cast film; in this embodiment, P-PW 12 The mixed solution has a solid content of 0.08 mg / mL to 0.1 mg / mL.

[0066] In the fifth step, part of the cast film is cut into several pieces, and a silver nanowire suspension of a certain concentration is sprayed on each piece to obtain P-PW 12 / AgNWs-x composite film, wherein x corresponds to the concentration of AgNWs; in the spraying of this embodiment, the cast film is fixed on the tinplate sheet heated at a constant temperature. The cast film is fixed on the tinplate sheet heated at a constant temperature, and the temperature of the constant temperature heating is 60-80°C.

[0067] During spraying, the distance between the spray gun and the film is at least 9-12 cm, and the spraying pressure is 0.2-0.5 MPa.

[0068] In the sixth step, the remaining parts are formed into upper and lower substrates, which are respectively arranged on each P-PW 12 / AgNWs-x composite film on both sides, hot pressing, to obtain P-PW containing different concentrations of AgNWs 12 / AgNWs / P-PW 12 -x composite film.

[0069] In this embodiment, the temperature during hot pressing is 50-70° C., the pressure is 10-15 MPa, and the total hot pressing time is 20s-30s.

[0070] The P-PW obtained by the preparation method of the electromagnetic shielding film material with photochromic effect prepared in this embodiment 12 / AgNWs / P-PW 12 - Application of x composite films in the field of electronic equipment.

[0071] The application is specifically as a screen, and the screen can be used in different light intensity environments by adjusting the transmittance state.

[0072] Example 1

[0073] (1) First, weigh 1 g of polymethyl methacrylate (PMMA) particles into a beaker, add 10 mL of dichloromethane (CH2Cl2) organic solvent, and stir quickly with a glass rod for 1 min to make it evenly dispersed. Then stir with a magnetic stirrer (speed 650 rpm) at room temperature for 0.5 h until PMMA is completely dissolved and set aside. At the same time, weigh 0.05 g of phosphotungstic acid (PWA) particles into a beaker, add 0.68 mL of tetrahydrofuran (THF) organic solvent, and shake thoroughly to completely dissolve it. Pour it into the previously prepared PMMA solution and stir with a magnetic stirrer (speed 500 rpm) at room temperature for 5 min. P-PW is obtained. 12 Mix the solution.

[0074] (2) The silver nanowire dispersion (20 mg / mL) was diluted to different concentrations (1, 2, 3, 4 and 5 mg / mL) in an ethanol solution for use. The P-PW12 mixed solution was then evenly poured into a petri dish, dried for 6 hours, and peeled off to obtain a cast film. The PMMA film was cut into five parts, each with a size of 30 mm × 30 mm, and fixed on a tinplate sheet placed on a constant temperature heating platform (70°C). Then, a spray gun was used to evenly spray silver nanowire suspensions (1 mL) of different concentrations on the surface of the PMMA film at a distance of 10 cm and a pressure of 0.2 MPa. P-PW was obtained. 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs.

[0075] In this embodiment, within the concentration range of 1-5 mg / mL, silver nanowires and other components in the film (such as polymethyl methacrylate, phosphotungstic acid, etc.) can work well together. The appropriate concentration of silver nanowires can ensure electromagnetic shielding performance without affecting the performance of other components, such as maintaining the good mechanical properties of polymethyl methacrylate and the photochromic properties of phosphotungstic acid. If the concentration of silver nanowires is too high, it may destroy the structure or performance of other components and affect the performance balance of the overall film.

[0076] (3) In order to effectively protect the exposed silver nanowire conductive network, the prepared P-PW 12 The / AgNWs-x composite film and PMMA film were hot pressed under the conditions of temperature (68 °C), pressure (12 MPa), and time (20 s) to achieve the coating structure and successfully prepare P-PW 12 / AgNWs / P-PW 12 -x composite film.

[0077] Figure 1a-Figure 1c is a scanning electron microscope image, where Figure 1a A network structure composed of silver nanowires (AgNWs) is shown, densely and evenly distributed on the substrate surface. The nanowires are intertwined to form a conductive path. The nanowires are thin and uniform in diameter and randomly distributed. The density of the nanowires is evenly distributed, and no obvious agglomeration is observed. This network structure can significantly improve the conductivity and mechanical properties of the composite material. The uniform distribution helps to obtain stable electrical and optical properties.

[0078] Figure 1b Demonstrated P-PW 12 / AgNWs / P-PW 12 -x smooth surface covering structure, with Figure 1a The surface appears quite smooth and uniform, with no obvious defects or cracks. There are no signs of silver nanowires protruding from the surface, indicating that the nanowires are efficiently coated. The smooth surface may help improve the material's transparency and resistance to environmental corrosion. 12 As a covering layer, it can well conceal the internal structure and form a smooth surface.

[0079] Figure 1c The cross-section of the composite film is shown, including two layers of polymer (PMMA) and a silver nanowire layer (AgNWs) in the middle. It can be clearly seen that the material is divided into two layers of PMMA matrix, the upper and lower layers, and the nanowire network layer in the middle. The AgNWs layer is displayed as a highlighted linear area in the middle, indicating that the silver nanowires are mainly concentrated in a specific position. Interface bonding: The interface between the upper and lower layers of PMMA and the AgNWs layer is flat and well bonded, with no obvious stratification or gap. The design of the layered structure enhances the comprehensive properties of the composite material (such as conductivity, mechanical properties and transparency). It can be seen from the opening that the tightly bonded interface in this embodiment shows that the preparation process is proper, which helps to improve the overall mechanical strength and stability.

[0080] Figure 1d Energy dispersive X-ray spectroscopy (EDS): Figure 1dThe composite distribution of tungsten (W) and phosphorus (P) elements is shown.

[0081] Figure 1e Energy dispersive X-ray spectroscopy (EDS) only shows the individual distribution of tungsten (W) elements. Figure 1f The individual distribution of phosphorus (P) element is shown, from which it can be concluded that the tungsten element is evenly distributed on the substrate.

[0082] pass Figures 1a-1f It can be seen that the prepared P-PW 12 / AgNWs / P-PW 12 The silver nanowires of the composite film are uniformly distributed on the substrate, and the tungsten element is uniformly distributed on the substrate.

[0083] Figure 2a P-PW in stress-strain curve 12 / AgNWs / P-PW 12 -1 (lowest AgNWs concentration): The initial stress is the smallest, but when stretched to a higher strain, it shows the highest stress peak, indicating that the material is relatively tough. 12 / AgNWs / P-PW 12 -2: Slightly reduced strength compared to the lowest concentration material, but still maintains good stress levels. P-PW 12 / AgNWs / P-PW 12 -3: The stress decreases slightly, but still shows high tensile strength. P-PW 12 / Ag NWs / P-PW 12 -4: The stress intensity is further reduced, and the curve declines significantly, indicating that the material performance has deteriorated. 12 / AgNWs / P-PW 12 -5 (highest AgNWs concentration): shows the lowest tensile strength and strain capacity, indicating that too high AgNWs concentration will weaken the mechanical properties of the composite. It can be seen that with the increase of AgNWs concentration, the tensile stress of the material shows an overall downward trend. The right amount of AgNWs (such as 1 or 2 mg / mL) can enhance the mechanical properties of the composite, while too high a concentration will lead to deterioration of the performance, probably because the nanowires are over-stacked, affecting the uniformity and structural integrity of the composite.

[0084] Figure 2b The tensile stress bar graph and strain line show the tensile stress data at AgNWs concentrations of 1, 2, 3, 4, and 5 mg / mL from left to right. The tensile stress gradually decreases from 25.98 MPa (concentration 1) to 22.36 MPa (concentration 5). This indicates that the bearing capacity of the material gradually decreases with the increase of AgNWs concentration. Line graph (fracture strain%): indicates the deformation capacity of the material before tensile fracture.

[0085] The strain almost remained at a low level from concentration 1 to 5, concentrated below 2.5%. This shows that increasing the concentration of AgNWs has almost no significant improvement on the ductility of the material. Lower AgNWs concentration (1 or 2 mg / mL) helps to improve the tensile strength of the material, but too high a concentration will reduce the mechanical properties of the composite material. The strain capacity does not change significantly at different concentrations, and the ductility of the material is relatively stable.

[0086] like Figure 2a-2d As shown, it can be seen that the obtained P-PW 12 / AgNWs / P-PW 12 The composite film has good tensile strength (25MPa), which meets the mechanical properties of transparent electromagnetic shielding film P-PW 12 / AgNWs / P-PW 12 The composite film still exhibits good mechanical strength and high optical transparency when bent.

[0087] Example 2

[0088] (1) First, weigh 1 g of polymethyl methacrylate (PMMA) particles into a beaker, add 10 mL of dichloromethane (CH2Cl2) organic solvent, and stir quickly with a glass rod for 1 min to make it evenly dispersed. Then stir with a magnetic stirrer (speed 650 rpm) at room temperature for 0.5 h until PMMA is completely dissolved and set aside. At the same time, weigh 0.05 g of phosphotungstic acid (PWA) particles into a beaker, add 0.68 mL of tetrahydrofuran (THF) organic solvent, and shake thoroughly to completely dissolve it. Pour it into the previously prepared PMMA solution and stir with a magnetic stirrer (speed 500 rpm) at room temperature for 5 min. P-PW is obtained. 12 Mix the solution.

[0089] (2) The silver nanowire dispersion (20 mg / mL) was diluted to different concentrations (1, 2, 3, 4 and 5 mg / mL) in an ethanol solution for use. The P-PW12 mixed solution was then evenly poured into a petri dish, dried for 6 hours, and peeled off to obtain a cast film. The PMMA film was cut into five parts, each with a size of 30 mm × 30 mm, and fixed on a tinplate sheet placed on a constant temperature heating platform (70°C). Then, a spray gun was used to evenly spray silver nanowire suspensions (1 mL) of different concentrations on the surface of the PMMA film at a distance of 10 cm and a pressure of 0.2 MPa. P-PW was obtained. 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs.

[0090] (3) In order to effectively protect the exposed silver nanowire conductive network, the prepared P-PW12 The / AgNWs-x composite film and PMMA film were hot pressed under the conditions of temperature (68 °C), pressure (12 MPa), and time (20 s) to achieve the "sandwich" structure coating and successfully prepare P-PW 12 / AgNWs / P-PW 12 -x composite film.

[0091] The optical properties of the composite films prepared in the examples of the present invention were tested, and the transmittance of the composite films with different silver nanowire loadings was measured in the visible light wavelength range (400-800 nm).

[0092] See attached Figure 3a At low concentrations (1 mg / mL), the transmittance decreases slightly, ranging from 85% to 90%. The transmittance at a wavelength of 400nm is low, about 85%, and the transmittance gradually increases as the wavelength increases, approaching 90% at 800nm. Compared with PMMA, the transparency is slightly reduced, but it still has good optical properties. Concentration 2mg / mL: The transmittance further decreases, ranging from 80% to 85%. At a concentration of 3mg / mL, the transmittance drops to 78% to 83%. As the concentration increases, the increase in transmittance with increasing wavelength slows down. High concentration AgNWs (4-5mg / mL) curve: Concentration 4mg / mL; The transmittance is significantly reduced, ranging from 75% to 80%, and the optical transparency is significantly reduced compared with the low concentration sample. Concentration 5mg / mL: The transmittance is further reduced, about 70% at a wavelength of 400nm, and only reaches 75% at 800nm. The transparency decreases more significantly, and the material gradually becomes opaque.

[0093] See attached Figure 3b As shown, the transparency is good at low concentrations (1-2 mg / mL), which is suitable for scenarios that require both optical transparency. At high concentrations (3-5 mg / mL), the optical transparency is significantly reduced, but the electromagnetic shielding performance may be significantly improved. For applications that require both transparency and electromagnetic shielding performance, 1-2 mg / mL can be selected. If the transparency requirement is lower and the shielding performance is preferred, 3-5 mg / mL can be selected.

[0094] like Figure 3a-3e As shown in the figure, especially the photos of the composite membranes under different reference materials in 3c-3c, when the silver nanowire loading is 1 mg / mL, P-PW 12 / AgNWs / P-PW 12 The transmittance of the composite film reached a maximum of 87.7%, but even at a silver nanowire loading of 5 mg / mL, the composite film still maintained a relatively high transmittance (>79.7%), which indicates that the invention has excellent optical properties.

[0095] Example 3

[0096] (1) First, weigh 1 g of polymethyl methacrylate (PMMA) particles into a beaker, add 10 mL of dichloromethane (CH2Cl2) organic solvent, and stir quickly with a glass rod for 1 min to make it evenly dispersed. Then stir with a magnetic stirrer (speed 650 rpm) at room temperature for 0.5 h until PMMA is completely dissolved and set aside. At the same time, weigh 0.05 g of phosphotungstic acid (PWA) particles into a beaker, add 0.68 mL of tetrahydrofuran (THF) organic solvent, and shake thoroughly to completely dissolve it. Pour it into the previously prepared PMMA solution and stir with a magnetic stirrer (speed 500 rpm) at room temperature for 5 min. P-PW is obtained. 12 Mix the solution.

[0097] (2) The silver nanowire dispersion (20 mg / mL) was diluted to different concentrations (1, 2, 3, 4 and 5 mg / mL) in an ethanol solution for use. The P-PW12 mixed solution was then evenly poured into a petri dish, dried for 6 hours, and peeled off to obtain a cast film. The PMMA film was cut into five parts, each with a size of 30 mm × 30 mm, and fixed on a tinplate sheet placed on a constant temperature heating platform (70°C). Then, a spray gun was used to evenly spray silver nanowire suspensions (1 mL) of different concentrations on the surface of the PMMA film at a distance of 10 cm and a pressure of 0.2 MPa. P-PW was obtained. 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs.

[0098] (3) In order to effectively protect the exposed silver nanowire conductive network, the prepared P-PW 12 The / AgNWs-x composite film and PMMA film were hot pressed under the conditions of temperature (68 °C), pressure (12 MPa), and time (20 s) to achieve the "sandwich" structure coating and successfully prepare P-PW 12 / AgNWs / P-PW 12 -x composite film.

[0099] The electromagnetic shielding performance of the composite film prepared in the embodiment of the present invention was tested, and the electromagnetic shielding performance exhibited in the X-band is shown in FIG4 , wherein Figure 4a Before hot pressing: the surface density of Ag NWs is 0.1 mg / cm 2 When the surface density increases to 0.6 mg / cm 2 , the sheet resistance gradually decreased to 48.9Ω / sq. The overall trend was downward, but the conductivity before hot pressing was significantly lower than that after hot pressing. After hot pressing: at 0.1mg / cm 2When the sheet resistance drops significantly from 160.2Ω / sq to 92.5Ω / sq. The surface density is 0.6mg / cm 2 When the sheet resistance is further reduced to 38.4Ω / sq. The hot pressing treatment significantly improves the connectivity and conductivity of the AgNWs network. The conductivity increases with the increase of the surface density of AgNWs: the increase in surface density means that more AgNWs form a dense network, which reduces the resistance. Hot pressing significantly improves the conductive properties: the compaction process reduces the contact resistance between AgNWs.

[0100] See attached Figure 4b As shown in the figure: EMI SE value gradually increases with the increase of AgNWs concentration, and the shielding effectiveness decreases slightly with the increase of frequency. Concentration is 1mg / mL: EMI SE is the lowest, only about 12-14dB. 5mg / mL: reaches the highest value, about 24-26dB. As the concentration of Ag NWs increases, the shielding effectiveness is significantly improved. High concentration forms a denser shielding layer, which enhances the reflection and absorption performance. The frequency dependence is small, and the effect of frequency on shielding effectiveness is relatively limited in the range of 8-12GHz.

[0101] See attached Figure 4c As shown, it can be seen that with the increase of AgNWs concentration, the total shielding effectiveness increases from 13.5dB (1mg / mL) to 24.1dB (5mg / mL). The absorption efficiency (SE_A) gradually dominates, increasing from 8.0dB (1mg / mL) to 16.2dB (5mg / mL). The reflection efficiency (SE_R) changes slightly, about 3.5-5.0dB. Absorption / reflection ratio: The absorption ratio increases with increasing concentration, from 68% (1mg / mL) to 75% (5mg / mL). The reflection ratio decreases accordingly, from 32% to 25%. Absorption is the dominant mechanism: The high-concentration AgNWs shielding layer has a higher absorption efficiency ratio, and shielding is mainly achieved by dissipating electromagnetic wave energy. Reflection contribution is small: Reflection mainly comes from the good conductivity of AgNWs, but its contribution is limited compared to the absorption effect.

[0102] See attached Figure 4d As shown, it can be seen that the shielding effectiveness is the highest in the initial state, about 24-26dB, and decreases slightly with the increase of frequency. After 20 days of storage: the shielding effectiveness decreases slightly, about 1-2dB. After 40 days of storage: the overall shielding effectiveness decreases further, about 3-4dB. Range of change: the attenuation of shielding effectiveness gradually increases with time, but the decline is small, indicating that the performance of the material is relatively stable. Good long-term stability: AgNWs-based shielding film still maintains a high shielding effectiveness (about 20dB or more) within 40 days. Reason for slight attenuation: It may be related to the oxidation of AgNWs or the slight looseness of the network structure.

[0103] The electromagnetic shielding performance of the composite film prepared in the embodiment of the present invention is tested, and the electromagnetic shielding performance exhibited in the X-band is as follows: Figures 4a-4d As shown, when the silver nanowire content is 5 mg / mL, P-PW 12 / AgNWs / P-PW 12 The electromagnetic shielding effectiveness value of the composite film increases to a maximum value of 24.1 dB, and the effective shielding bandwidth can cover the entire X-band (8.2-12.4 GHz), which indicates that the invention has excellent shielding performance.

[0104] Example 4

[0105] (1) First, weigh 1 g of polymethyl methacrylate (PMMA) particles into a beaker, add 10 mL of dichloromethane (CH2Cl2) organic solvent, and stir quickly with a glass rod for 1 min to make it evenly dispersed. Then stir with a magnetic stirrer (speed 650 rpm) at room temperature for 0.5 h until PMMA is completely dissolved and set aside. At the same time, weigh 0.05 g of phosphotungstic acid (PWA) particles into a beaker, add 0.68 mL of tetrahydrofuran (THF) organic solvent, and shake thoroughly to completely dissolve it. Pour it into the previously prepared PMMA solution and stir with a magnetic stirrer (speed 500 rpm) at room temperature for 5 min. P-PW is obtained. 12 Mix the solution.

[0106] (2) The silver nanowire dispersion (20 mg / mL) was diluted to different concentrations (1, 2, 3, 4 and 5 mg / mL) in an ethanol solution for use. The P-PW12 mixed solution was then evenly poured into a petri dish, dried for 6 hours, and peeled off to obtain a cast film. The PMMA film was cut into five parts, each with a size of 30 mm × 30 mm, and fixed on a tinplate sheet placed on a constant temperature heating platform (70°C). Then, a spray gun was used to evenly spray silver nanowire suspensions (1 mL) of different concentrations on the surface of the PMMA film at a distance of 10 cm and a pressure of 0.2 MPa. P-PW was obtained. 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs.

[0107] (3) In order to effectively protect the exposed silver nanowire conductive network, the prepared P-PW 12 The / AgNWs-x composite film and PMMA film were hot pressed under the conditions of temperature (68 °C), pressure (12 MPa), and time (20 s) to achieve the "sandwich" structure coating and successfully prepare P-PW 12 / AgNWs / P-PW 12 -x composite film.

[0108] The Joule heating performance test was performed on the composite film prepared in the embodiment of the present invention. Figure 5a-5e The material was shown to be able to reach a stable surface temperature from room temperature in a short time (about 20 seconds). Figure 5a It can be seen that as the voltage increases, the peak temperature gradually increases. The temperature rises rapidly after power is turned on and stabilizes after reaching the peak. When the voltage is low (2.5V), the temperature rises slowly and the peak temperature is low. Therefore, the higher the voltage, the faster the material heats up and the higher the final temperature, indicating that the voltage is positively correlated with the material's heating capacity. Figure 5b As shown in the figure, the data points are basically distributed linearly and are represented by a linear fitting curve. The temperature rise characteristic of the material is proportional to the square of the voltage. Figure 5c As shown in the figure, it shows the temperature change curve when the voltage is gradually increased and decreased. The voltage is sequentially increased to 4.5V and then gradually decreased to 2.5V, and the temperature rises and falls in a step-like manner. The temperature response voltage changes rapidly, indicating that the thermal response speed of the material is high. The heating and cooling process of the material has good reversibility, indicating that its thermal performance is stable. Figure 5d As shown in the figure, it is an infrared thermal image, which shows the thermal distribution of the material under high temperature conditions. The uniformity of temperature distribution and hot spots can be seen in the image. The maximum temperature is 48.7℃ and the minimum temperature is 18.5℃. It can be concluded that the thermal imaging shows that the material surface is heated evenly, and there may be slight hot spots in some parts. Figure 5e As shown in the figure, it shows the temperature stability of the material under a long-term constant voltage (such as 4.5V) over time, and is accompanied by thermal distribution diagrams at multiple times. After the initial increase, the temperature gradually stabilizes between 51.2℃ and 52.2℃, with small fluctuations. The temperature distribution does not change much. The material shows good thermal stability and uniformity when working for a long time.

[0109] It was found that there is an approximate linear relationship between the saturation temperature and the square of the input voltage, and the surface temperature remains evenly distributed during the bending deformation process, and the steady-state temperature can last for nearly 720 seconds, indicating that the composite film of this invention has excellent Joule heating performance.

[0110] Example 5

[0111] (1) First, weigh 1 g of polymethyl methacrylate (PMMA) particles into a beaker, add 10 mL of dichloromethane (CH2Cl2) organic solvent, and stir quickly with a glass rod for 1 min to make it evenly dispersed. Then stir with a magnetic stirrer (speed 650 rpm) at room temperature for 0.5 h until PMMA is completely dissolved and set aside. At the same time, weigh 0.05 g of phosphotungstic acid (PWA) particles into a beaker, add 0.68 mL of tetrahydrofuran (THF) organic solvent, and shake thoroughly to completely dissolve it. Pour it into the previously prepared PMMA solution and stir with a magnetic stirrer (speed 500 rpm) at room temperature for 5 min. P-PW is obtained. 12 Mix the solution.

[0112] (2) The silver nanowire dispersion (20 mg / mL) was diluted to different concentrations (1, 2, 3, 4 and 5 mg / mL) in an ethanol solution for use. The P-PW12 mixed solution was then evenly poured into a petri dish, dried for 6 hours, and peeled off to obtain a cast film. The PMMA film was cut into five parts, each with a size of 30 mm × 30 mm, and fixed on a tinplate sheet placed on a constant temperature heating platform (70°C). Then, a spray gun was used to evenly spray silver nanowire suspensions (1 mL) of different concentrations on the surface of the PMMA film at a distance of 10 cm and a pressure of 0.2 MPa. P-PW was obtained. 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs.

[0113] (3) In order to effectively protect the exposed silver nanowire conductive network, the prepared P-PW 12 The / AgNWs-x composite film and PMMA film were hot pressed under the conditions of temperature (68 °C), pressure (12 MPa), and time (20 s) to achieve the "sandwich" structure coating and successfully prepare P-PW 12 / AgNWs / P-PW 12 -x composite film.

[0114] The photochromic performance of the composite film prepared in the embodiment of the present invention was tested. Figure 6a-6f As shown, the P-PW under ultraviolet light (λ = 400 ~ 800nm) was measured 12 / AgNWs / P-PW 12 -3 The UV-vis absorption spectrum of the composite film shows that the absorption intensity at 470nm and 730nm wavelengths gradually increases. The UV dose is 120kJ / m 2The absorbance reaches saturation when the absorbance is 0.58. After irradiation with ultraviolet light, the absorbance at a wavelength of 730nm does not decrease significantly after 10 repetitions, indicating that the composite film has excellent anti-fatigue performance. It indicates that the composite film of the present invention can be applied to the field of smart windows. While ensuring high transparency and shielding electromagnetic waves, the modulation of ultraviolet light can also improve indoor daylight comfort, save energy, and achieve low-carbon and environmentally friendly effects.

[0115] The present invention focuses on transparent electromagnetic shielding materials, combines PMMA and PWA to prepare photochromic films, and demonstrates that these highly transparent and photosensitive photochromic films used as casting coatings and inkjet printing are supplemented with photochromic functions to prepare polymer-based electromagnetic shielding composite films with photochromic effects. By controlling the loading amount of silver nanowires, the optical properties and electromagnetic shielding properties of the composite film can be jointly regulated.

[0116] The electromagnetic shielding film material with photochromic effect prepared by the present invention can be applied in the field of electronic equipment. With the popularity of smart phones and tablet computers, people have higher and higher requirements for the functions and performance of the equipment. The film material prepared in the present invention can be applied to the surface of the screen as a protective and functional enhancement layer. In daily use, it can effectively shield external electromagnetic interference, prevent damage to the internal electronic components of the device, and improve the stability of the device operation. At the same time, its photochromic effect can automatically adjust the transparency and color of the screen according to the intensity of the ambient light, darken in strong light to reduce glare, improve screen visibility, and protect the user's eyes; brighten in low light environment to ensure the clarity of the screen display. For example, when the sunlight is strong outdoors, the screen automatically adjusts to a low transmittance state, so that the screen content is still clearly visible, and can effectively prevent the aging effect of ultraviolet rays on the screen; when the light indoors is dim, the screen restores high transmittance to provide a good visual experience.

[0117] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0118] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing an electromagnetic shielding film material having a photochromic effect, characterized in that: The following steps are included: The mixture of transition metal oxide and polar organic solvent is added to polymethyl methacrylate solution and stirred magnetically to obtain P-PW 12 Mixing solutions; Diluting the silver nanowire dispersion in an ethanol solution to different concentrations to form a plurality of silver nanowire suspensions, wherein the different concentrations range from 1 mg / mL to 5 mg / mL; In a petri dish, pour P-PW 12 mixing the solutions to obtain a cast film; Part of the cast film is cut into several pieces, and a silver nanowire suspension of a certain concentration is sprayed on each piece to obtain P-PW 12 / AgNWs-x composite films, where x corresponds to the concentration of AgNWs; The rest of the parts form upper and lower substrates, which are respectively arranged on each P-PW 12 / AgNWs-x composite film on both sides, hot pressing, to obtain P-PW containing different concentrations of AgNWs 12 / AgNWs / P-PW 12 -x composite film.

2. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 1, characterized in that: The method also includes the preparation of a polymethyl methacrylate solution, specifically, the polymethyl methacrylate particles and a halogenated hydrocarbon solvent are mixed and stirred to be uniformly dispersed, and then the polymethyl methacrylate solution is added, and magnetic stirring is performed to obtain a P-PW12 mixed solution.

3. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 2, characterized in that: The mass ratio of the phosphotungstic acid particles to the polymethyl methacrylate particles is 15:1-25:

1.

4. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 1, characterized in that: The transition metal oxide includes phosphotungstic acid particles, and the polar organic solvent includes tetrahydrofuran, dichloromethane, acetone, ethyl acetate or N,N-dimethylformamide.

5. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 1, characterized in that: The magnetic stirring time is 3-7 min, and the speed is 400-600 rpm.

6. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 1, characterized in that: The P-PW 12 The mixed solution has a solid content of 0.08 mg / mL to 0.1 mg / mL.

7. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 1, characterized in that: During the spraying, the cast film is fixed on a tinplate sheet that is heated at a constant temperature, and the temperature of the constant temperature heating is 60-80°C.

8. The method for preparing the electromagnetic shielding film material with photochromic effect according to claim 1, characterized in that: During the spraying, the distance between the spray gun and the film is at least 9-12 cm, and the spraying pressure is 0.2-0.5 MPa.

9. The P-PW obtained by the method for preparing an electromagnetic shielding film material with photochromic effect as claimed in any one of claims 1 to 8 12 / AgNWs / P-PW 12 - Application of x composite films in the field of electronic equipment.

10. The use according to claim 9, characterized in that: The application is specifically as a screen, and the screen can be used in different light intensity environments by adjusting the transmittance state.

Citation Information

Patent Citations

  • Method for simultaneously preparing tungsten oxide quantum dot and tungsten oxide nanowire

    CN107055618A

  • Preparation method of stretchable flexible transparent electrochromic film

    CN110802903A

  • Flexible silver nanowire transparent electromagnetic shielding film and preparation method thereof

    CN113185729A

  • Viscoelastic polymer composite conductive material as well as preparation method and application thereof

    CN114773823A

  • Electrochromic device and method of manufacturing the same

    KR1020130066755A